2022
DOI: 10.3390/ijerph191710540
|View full text |Cite
|
Sign up to set email alerts
|

Has Smartphone Use Influenced Loneliness during the COVID-19 Pandemic in Japan?

Abstract: The influence of smartphone use on increased risk of feeling lonely has been recognized as a global public health concern. However, it is unclear whether this influence has changed during the ongoing COVID-19 pandemic, during which smartphones have become a particularly important means of communication due to health safety measures restricting personal interactions. We used Hiroshima University’s online survey data collected from 18–28 February 2022, to assess the impact of smartphone use on loneliness in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…Recent research has shown that smartphone usage helped alleviate the risk of experiencing loneliness amid the COVID-19 pandemic [1,2]. These results contradict previous research before the pandemic, which demonstrated that greater smartphone usage increased the risk of loneliness [3,4].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Recent research has shown that smartphone usage helped alleviate the risk of experiencing loneliness amid the COVID-19 pandemic [1,2]. These results contradict previous research before the pandemic, which demonstrated that greater smartphone usage increased the risk of loneliness [3,4].…”
Section: Introductionmentioning
confidence: 74%
“…The primary independent variable was smartphone use, assessed in minutes per day with the question, "On average, how many hours do you use your smartphone per day?" Additionally, as control variables, we incorporated gender, age, presence of children, residence, years of education, and financial literacy, all of which served as indicators of rational financial and health behaviors [1,23,24], drawing from the 2020 dataset. For the 2022 and 2023 waves, we expanded the set of control variables to encompass marital status, living status, employment status, household financial status, subjective health status, depression, future anxiety, financial satisfaction, and a myopic view of the future.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted December 14, 2022. ; https://doi.org/10.1101/2022.12.14.22283455 doi: medRxiv preprint loneliness during a pandemic, [38] a study conducted in Belgium during the COVID-19 pandemic that showed that those who felt lonely were more likely to use social media to cope with a lack of social contact,[39] and a study conducted in Australia during the COVID-19 pandemic reported lower levels of adolescent loneliness among those who used technology to connect with society. [40] Thus, in the extraordinary situation of the COVID-19 pandemic, it is possible that young people were not dependent on social media, but rather used it as a tool to combat loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness may favor the likelihood in developing depressive and anxiety disorders, alcohol and/or substance use and abuse, as well as incentivizing smoking habits [39]. Both these dimensions have been further investigated due to their dramatic increase among young people, particularly during the COVID-19 pandemic [38,[40][41][42][43][44]. Moreover, recent studies also explored the potential association between the boredom and loneliness dimensions with PIU, suggesting a hypothetical mediatory role of both dimensions in the onset and maintenance of PIU in vulnerable people, or suggesting the moderated role of distress tolerance in the association between PIU and boredom proneness/loneliness [36], even though there are not currently studies specifically investigating both dimensions together in PIU in Italian young adults [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%